Research on Compound Sliding Mode Control of a Permanent Magnet Synchronous Motor in Electromechanical Actuators - Jiachun Lin (MDPI AG, 2021)
In order to improve the response speed and disturbance rejection ability of a permanent magnet synchronous motor (PMSM) in an electromechanical actuator (EMA), a compound sliding mode control (CSMC) is proposed. The CSMC consists of a sliding mode controller with a new reaching law and disturbance observer based on a symmetric S-type function. The stability of the CSMC is analyzed using the Lyapunov stability analysis. The effectiveness of the CSMC is confirmed by the Simulink simulation, and experiments were conducted on a semi-physical platform. The results obtained by comparing the CSMC with the proportional integral (PI) control and traditional sliding mode control show that the CSMC has a faster response and stronger disturbance rejection ability and reduces chattering.